Toxic properties of insectoakaricidic preparation of ektosan - Євстаф’єва, В. О. (Scientific Progress & Innovations, 2012)
The data on the toxic properties of the insectoakaricidic preparation of ektosan have been received. The drug in therapeutic concentrations (0.13 % aqueous solution) showed no local irritation and resorptive effect on two species of animals (rabbits, rats). As for the local effect on the skin of laboratory animals under a single application ektosan was referred to the zero class and characterized by the absence of irritation. In the group of white rats an anxiety, weak erythema and considerable itch were registered in one animal in 15 minutes after treatment with this preparation, which disappeared in 30 minutes after their appearance.